Enhancing Survival Rate and Growth of Kopyor Coconut Plantlet Acclimatization Using Biostimulants - Maya Sinta, Masna; Riyadi, Imron; Widiastuti, Happy; Prasetyo, Muhammad Eko Riyo Bayu (Jurnal Ilmu Pertanian Indonesia, 2025)
In vitro embryo cultivation is the principal method for reproducing the kopyor coconut, an indigenous Indonesian species. Acclimatization is a critical step in this approach. The purpose of this study was to improve the survival and development rate of kopyor coconut seedlings grown in vitro during the acclimatization phase by using biological, organic, and mixed organic-biological biostimulants. This study employed a completely randomized block design that comprised the inclusion of biological, organic, and mixed biological-organic biostimulants, with no biostimulant as a control. The biological stimulant employed in this study was arbuscular mycorrhizal fungus (AMF), while the organic biostimulant was seaweed extract. Each treatment had 50 plantlets in triplicate. The results demonstrated that the treatment of biological and organic biostimulants increased plantlet survival rates during acclimatization, beginning 2 months after application and remaining consistent for 4 months. The biological stimulant application produced the highest plantlet survival rate (>94%). Based on how quickly the plantlets transitioned to the next stage, it was discovered that after 2-months incubation, most of the plantlets had already transferred to the second phase of acclimatization (opened tunnel). After 4-months incubation, the biological stimulant treatment produced the most plantlets at the later stage. However, throughout the 4-month acclimation period, more plantlets were transported from the pre-nursery to the main nursery, particularly with the use of organic biostimulants (56-64%). Keywords: arbuscular mycorrhizal fungi, plantlet, survival rate, seaweed